A Descriptive Cross-Sectional Study on Awareness and Belief of People About Cancer in Southern Ethiopia: Special Focus on Breast and Cervical Cancers - Labisso WL; Leka Y; Leka Y; Haileselassie W (Dove Medical Press, 2020)
Wajana Lako Labisso,1 Yishak Leka,2 Yohannes Leka,3 Werissaw Haileselassie4 1Department of Pathology, School of Medicine, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Pathology, College of Health Sciences and Medicine, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 3Department of Medical Microbiology, College of Health Sciences and Medicine, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 4Department of Reproductive Health and Health Service Management, School of Public Health, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Wajana Lako LabissoDepartment of Pathology, School of Medicine, College of Health Sciences, Addis Ababa University, EthiopiaTel +251966334092Email wajana.lako@aau.edu.etBackground: The general population’s lack of awareness, limited knowledge, myths and misconceptions about breast and cervical cancers (CCs) is considered as a serious public health problem.Objective: This study was intended to assess the status of awareness and beliefs of people about cancer and breast and CCs in particular.Methods: A descriptive community-based cross-sectional survey was conducted on 345 study participants in Southern Ethiopia. A pretested, structured questionnaire that contained demographics and questions on the variables of exposure to biological and chemical carcinogenic agents, lifestyle and personal behavior was administered. Frequency distribution and proportions were used to describe the study population in relation to major variables.Results: The mean age of study participants was 25.19 (Range 15– 58). More than a third of the study participants heard about cancer from Mass Media followed by schools (28.5%) and treating physicians (6.7%). The proportion of study participants that knew about the association between smoking, alcohol intake and cancer development was 38.6% and 51.5%, respectively. Only 48% and 24.2% of the study participants heard about breast and CCs, respectively. The fact that 69.4% of the study participants had limited knowledge about the mode of transmission of the causative agents of CCs indicates that the study groups are at risk of acquiring the agent. Additionally, only 4.7% of the study participants were screened for CC and have poor breast self-examination experiences, indicating poor awareness and knowledge about the importance of screening programs.Conclusion: Comprehensive awareness and knowledge about cancer in general and breast and CCs in particular is lacking in southern Ethiopia. Early sexual debut, limited knowledge about the diseases and unfavorable lifestyle are the risk factors to be addressed in public health education.Keywords: cervical cancer, breast cancer, southern Ethiopia, cancer awareness